2018
DOI: 10.2169/internalmedicine.0333-17
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study on the Epidemiological and Clinical Features of Emergency Patients with Large or Massive Consumption of Caffeinated Supplements or Energy Drinks in Japan

Abstract: Objective We conducted a retrospective study on the epidemiological and clinical features of patients with acute caffeine poisoning in Japan. Methods Letters requesting participation were sent to 264 emergency departments of hospitals, and questionnaires were mailed to those that agreed to participate. Patients Participants were patients transported to emergency departments of hospitals between April 2011 and March 2016 after consuming large or massive amounts of caffeinated supplements and/or energy drinks (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…While this result was somewhat anticipated (products promote the presence of caffeine), approximately half the PWS products investigated appeared likely to expose consumers to potential caffeine‐related harms. Recent public health recommendations for caffeine (eg, single doses <200 mg and daily consumption <400 mg (except pregnant women) reflect concerns over the increased availability of caffeinated products (eg, energy drinks) and increases in the frequency of caffeine‐related adverse events (including sleeping disturbance, anxiety, cardiovascular events, seizures, and death) . While no published evidence is available indicating the prevalence of PWS‐derived adverse events, anecdotally, the popularity and diversity of PWS continues to increase and recent case reports of adverse events linked to PWS consumption raise concern .…”
Section: Discussionmentioning
confidence: 99%
“…While this result was somewhat anticipated (products promote the presence of caffeine), approximately half the PWS products investigated appeared likely to expose consumers to potential caffeine‐related harms. Recent public health recommendations for caffeine (eg, single doses <200 mg and daily consumption <400 mg (except pregnant women) reflect concerns over the increased availability of caffeinated products (eg, energy drinks) and increases in the frequency of caffeine‐related adverse events (including sleeping disturbance, anxiety, cardiovascular events, seizures, and death) . While no published evidence is available indicating the prevalence of PWS‐derived adverse events, anecdotally, the popularity and diversity of PWS continues to increase and recent case reports of adverse events linked to PWS consumption raise concern .…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, pills do not injure the esophagus directly if they pass rapidly through esophagus into the stomach. A previous report reported that 97 of 101 patients with acute caffeine intoxication in Japan had consumed caffeine in tablet form [1]. Therefore, patients in Japan are at a high risk of caffeineinduced acute esophageal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Caffeine tablets are sold as over-the-counter supplements, and they are thought to be safe when consumed according to the manufacturers' instructions (less than 500 mg/day) [24]. However, acute caffeine intoxication has been occurring more frequently than previously in Japan, as well as in other countries, due to excessive caffeine ingestion (2 g or more) [1,24]. Plasma caffeine concentrations of more than 80-200 mg/L are considered lethal [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caffeine is a natural alkaloid that is obtained from coffee beans, tea leaves, cocoa beans, and kola nuts [1, 2]. It is included in drinks, prescription, and over-the-counter drugs, as well as weight loss supplements [2].…”
Section: Introductionmentioning
confidence: 99%